Model for virtual corporations partner selection based on adaptive genetic algorithm - LI Jian1; JING Bo2; NIU Shao-zhang1; YANG Yi-xian1 (Tongxin xuebao)
To enhance the efficiency of corporation partner selection and optimization process in virtual corporations, an partner selection process and optimizations model for virtual corporations based on adaptive genetic algorithm were pre-sented. In the model, the adaptive genetic algorithm was used to enhance the efficiency of corporation partner selection and optimization process. The AGA could solve the problem of prematurity and local convergence more compatibly than SGA. In the experiments, two kinds of genetic algorithms were used to be compared with, which were standard genetic algo-rithm（SGA） and adaptive genetic algorithm（AGA）. After 1 000 times of experiments to gain the optimal result, SGA aver-agely needed 166 runs, while the AGA averagely only needed 145 runs. The experimental results show that the AGA can gain the optimal result more efficiently than SGA in corporation partner selection and optimization process.